Axillary Block as the Sole Anesthetic for Peripherally Inserted Central Catheter Placement in an Infant with Goldenhar Syndrome - Ma. Carmen Bernardo-Ocampo (Case Reports in Anesthesiology)
The use of peripheral nerve block as the sole anesthetic in infants is not very common. Studies have demonstrated that ultrasound guided (USG) peripheral nerve block is associated with higher overall success rate when compared with nerve stimulation (Rubin et al., 2009, and Gelfand et al., 2011). Described below is a medically complex infant who had an USG axillary brachial plexus block for peripherally inserted central catheter (PICC) placement.